RESPONSE OF BOLLWORMS AGAINST TRANSGENIC Bt COTTON IN THE CENTRAL TELANGANA AGRO CLIMATIC ZONE OF ANDHRA PRADESH - REDDY, G.V. KRISHNA; SURYAKALA, I.; SHESHAIAH, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Studies on population dynamics of boll worms on transgenic Bt cotton viz. American bollworm, also called false America bollworm or old world bollworm, Helicoverpa armigera (Hubner). pink bollworm, Pectinophora gossypiella (Saunders), and the leaf worm, Spodoptera litura (Fabr.) is mainly a foliage feeder but it also damages cotton bolls were carried out in the farmers fields under unprotected conditions in the Central Telangana agro climatic Zone of Andhra Pradesh during 2010-11 Kharif season. The incidence of bollworms began 100 Days after sowing. The moderate incidence of Spodoptera litura was recorded (0.02 to 3.2 larvae Plant). Low level of Pectinophora gossypiella (0.01 to 0.092 larvae plant) and very low level of Helicoverpa armigera as recorded (0.002 to 0.17 larvae plant). There is no significant difference of pest populations recorded between the various Bt cotton genotypes.